Differentiation between G3 pancreatic neuroendocrine tumor and pancreatic neuroendocrine carcinoma based on intratumor and peritumor CT value ratio and abnormal vascular network - Zhang, Chaoyang; Hao, Wei (Frontiers in Oncology, 2025)
BackgroundTo develop a model based on computed tomography (CT) images to differentiate between grade 3 (G3) pancreatic neuroendocrine tumors (pNETs) and pancreatic neuroendocrine carcinoma (pNECs).MethodsThis retrospective study included patients with pathologically confirmed pNETs and pNECs who underwent abdominal CT examinations at JINCHENG GENERAL Hospital between June 2012 and June 2023. Tumor and peri-tumor CT characteristics were assessed, including peri-tumor areas A (0–10 mm) and B (10–20 mm) during the arterial and portal venous phases of dynamic enhancement. A model was established using binary logistic regression and receiver operating characteristic (ROC) curves.ResultsA total of 42 patients were included: 20 with G3 pNETs and 22 with pNECs. The ROC analysis showed that the combination of the arterial phase CT ratio B1, portal venous phase CT ratio B2, pancreatic duct invasion (PDI), peripancreatic fat infiltration (PFI), and abnormal vascular network (AVN) [area under the ROC curve (AUC)=0.970 (95% confidence interval (CI): 0.927-1.000), sensitivity=95.50%, and specificity=90.00%] exhibited a better performance in identifying G3 pNETs and pNECs than the combination of the arterial phase CT ratio B1 and the portal venous phase CT ratio B2 [AUC = 0.907 (95% CI: 0.818-0.996), sensitivity=77.30%, and specificity=95.00%], and the combination of arterial phase CT ratio B1, portal venous phase CT ratio B2, and AVN [AUC = 0.923 (95% CI: 0.810-1.000), sensitivity=81.80%, and specificity=85.00%].ConclusionThe enhancement ratio between the tumor and peri-tumoral B area in the arterial and portal venous phases, along with AVN, PFI, and PDI, may serve as effective indicators for distinguishing pNECs from G3 pNETs.